Probing the relationship among reading anxiety, mindfulness, reflective thinking, and reading comprehension ability of Iraqi intermediate and advanced EFL learners - Hussein Kareem Alsharhani; Behzad Ghonsooly; Elham Naji Meidani (Peoples' Friendship University of Russia (RUDN University), 2023)
While students can benefit from mindfulness and reflective thinking practices in their academic success, few studies grasp the entire scope of individuals' experiences. The current study aimed to investigate the relationship among mindfulness, reflective thinking, reading anxiety, and reading comprehension ability‎ in two groups of lower intermediate and advanced Iraqi EFL learners. The research questions investigated role of mindfulness, reflective thinking, and foreign language reading anxiety in the reading comprehension ability of Iraqi EFL learners as well as the predicative power of these variables in EFL learners' success. The research also examined the effect of these variables on learners' level. Finally, learners' attitudes towards the investigated variables were reported. To meet the objectives of the study, mixed-methods research was employed. A total of 200 Iraqi EFL learners were selected and assigned to the experimental and control groups. Both groups were subjected to the reading anxiety comprehension scale, reflective thinking questionnaire, mindfulness scale, and iBT TOEFL reading tests. Data in the qualitative phase of the study were obtained from the semi-structured interviews. It was found that mindfulness and reflective thinking played a positive role in Iraqi EFL learners' reading comprehension, while reading anxiety could negatively affect it. There was a significant difference between Iraqi lower intermediate and advanced EFL learners concerning their mindfulness, reflective thinking, reading anxiety, and reading comprehension ability. Some of the themes arose from the analysis of the interview included working memory enhancement by mindfulness, meta-cognitive reading by reflective thinking, and fear of frustration by anxiety. In conclusion, variables of mindfulness, reflective thinking, and reading anxiety could affect the reading comprehension of EFL Arab learners at advanced and lower intermediate levels. Therefore, teachers are highly recommended to create an atmosphere in which pupils are relaxed and secure.